Women's basketball will 'dance' in Lubbock, Texas - Armbruster, Shirley::::::::: (2013)
The Fresno State women's basketball team will be the No. 15 seed in the Spokane Region, and open the 2013 NCAA Tournament against second-seeded California in Lubbock, Texas.